1985
DOI: 10.1073/pnas.82.11.3771
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of cDNAs for human aldehyde dehydrogenases 1 and 2.

Abstract: Partial cDNA clones encoding human cytosolic aldehyde dehydrogenase (ALDH1) and mitochondrial aldehyde dehydrogenase (ALDH2) were isolated from a human liver cDNA library constructed in phage Agtll. The expression library was screened by using rabbit antibodies against ALDH1 and ALDH2. Positive clones thus obtained were subsequently screened with mixed synthetic oligonudeotides compatible with peptide sequences of ALDH1 and ALDH2. One of the positive clones for ALDH1 contained an insertion of 1.6 kilobase pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(66 citation statements)
references
References 27 publications
1
65
0
Order By: Relevance
“…The information about the sequence involved in the [ 125 I]T 3 -binding site was obtained by the identification of the peptide with radioactivity after digestion of the affinity labeled xCTBP with lysyl endopeptidase. Protein sequencing revealed that the peptide (K)LADLVERDRLILSTM-, which corresponded well to 91-106 residues of human ALDH1 enzyme (25) and to 92-107 residues of xALDH1-I and -II enzymes Table I. xCTBP catalyzed the conversion of acetaldehyde into acetic acid or retinal into RA at a linear rate for at least 1-2 min at 1.85 g of the purified protein.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The information about the sequence involved in the [ 125 I]T 3 -binding site was obtained by the identification of the peptide with radioactivity after digestion of the affinity labeled xCTBP with lysyl endopeptidase. Protein sequencing revealed that the peptide (K)LADLVERDRLILSTM-, which corresponded well to 91-106 residues of human ALDH1 enzyme (25) and to 92-107 residues of xALDH1-I and -II enzymes Table I. xCTBP catalyzed the conversion of acetaldehyde into acetic acid or retinal into RA at a linear rate for at least 1-2 min at 1.85 g of the purified protein.…”
Section: Resultsmentioning
confidence: 76%
“…Screening of cDNA Library and Sequence Analysis-An hepatic cDNA library was screened with 32 P-radiolabeled human ALDH1 cDNA (25). The entire sequences of the two cDNAs were determined for both strands by the method of Sanger et al (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ALDH2*2 mutant allele is characterized by the loss of a Ksp632I restriction site and a resulting enzyme with little or no catalytic activity (Crabb et al, 1989;Hsu et al, 1985).…”
mentioning
confidence: 99%
“…Hsu et al, on the other hand, established the association of the oriental flush reaction with genetically determined absence of a mitochondria1 isoenzyme ALDH2, which is responsible for most acetaldehyde metabolism (33). There is no absence of this enzyme in Caucasians who exhibit an alcohol flush.…”
Section: Chlorpropamide-alcohol Flush ( C P a F )mentioning
confidence: 99%